Reduction of total harmonic reduction in torque characteristics in two-phase side by side brushless DC motor - Ng, Seng Shin (2013)
This research deals with the reduction of total harmonic distortion (THD) in torque characteristics for the improvement of torque ripple in two-phase side by side brushless DC motor. The sinusoidal waveform in torque characteristic create uniform flux distribution that produces smooth speed rotation. By creating an uniform flux distribution, the torque ripple produced by the motor is reduced. To reduce the torque ripple, the flux density distribution in the gap must be adjusted. It gives a more balanced flux density distribution in the motor. The ideal situation is that the developed torque being higher with low torque ripple value. By variation of various parameters, the flux flows inside the motor changes. The final aim is to get sinusoidal waveform and reduce the torque ripple as much as possible. Simulation studies to evaluate the aspects of the flux distribution inside the machine and the torque characteristic are presented. There are studies to reduce the cogging torque produced by the brushless DC motor. By reducing the cogging torque, the THD of the torque characteristic can be reduced. In those previous researches, the combination of each pole of different structure is not being discussed before. Thus, the combination method introduced in this research is a new technique that can further reduce the THD of the torque waveform produced by the motor. In this study, the structure of individual single phase brushless DC motor is adjusted to get near sinusoidal waveform in the torque characteristic which has low THD value. Combination of different pole structure motor is presented to get the lowest THD in torque characteristic possible. Then, two phase side by side brushless DC motor is presented to reduce the torque ripple produced by the motor. The simulation result in the original model is verified by experimental result. Simulation analysis using finite element method (FEM) is performed to analyze the magnetic circuit on various shapes of rotor and stator. The analysis parameters include the magnetic field flux, the cogging force and the developed torque. The optimum model is derived. In the end, the torque ripple generated by the original motor is reduced by 70.5% compared with the torque ripple produced by the optimized motor. So, the proper choice of parameters is important in getting sinusoidal waveform and reduce the torque ripple produced by the motor.